CD90/Thy-1, a Cancer-Associated Cell Surface Signaling Molecule - Sauzay, Chloé; Voutetakis, Konstantinos; Chatziioannou, Aristotelis; Chevet, Eric; Avril, Tony (Frontiers in Cell and Developmental Biology, 2019)
CD90 is a membrane GPI-anchored protein with one Ig V-type superfamily domain that was initially described in mouse T cells. Besides the specific expression pattern and functions of CD90 that were described in normal tissues, i.e., neurons, fibroblasts and T cells, increasing evidences are currently highlighting the possible involvement of CD90 in cancer. This review first provides a brief overview on CD90 gene, mRNA and protein features and then describes the established links between CD90 and cancer. Finally, we report newly uncovered functional connections between CD90 and endoplasmic reticulum (ER) stress signaling and discuss their potential impact on cancer development.